2006
DOI: 10.1200/jco.2005.03.3696
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Overall and Failure-Free Survival in Stage IV Follicular Lymphoma: 25 Years of Treatment Experience at The University of Texas M.D. Anderson Cancer Center

Abstract: Evolving therapy, including the incorporation of biologic agents, has led to stepwise significant outcome improvements for patients with advanced-stage follicular lymphoma. The apparent plateau in the FFS curve, starting approximately 8 to 10 years from the beginning of treatment, raises the issue of the potential curability of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
108
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(112 citation statements)
references
References 26 publications
2
108
1
1
Order By: Relevance
“…With advances in medical care, particularly with effective chemotherapy, patients with NHL can now live much longer. This survival benefit, documented in numerous clinical trials, [8][9][10][11][12][13][14][15][16][17][18][19][20] has been translated into the community effectiveness according to our population-based study. Patients receiving chemotherapy had a significantly lower risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in medical care, particularly with effective chemotherapy, patients with NHL can now live much longer. This survival benefit, documented in numerous clinical trials, [8][9][10][11][12][13][14][15][16][17][18][19][20] has been translated into the community effectiveness according to our population-based study. Patients receiving chemotherapy had a significantly lower risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The incidence of NHL has been increasing over the last several decades worldwide, [1][2][3][4][5][6][7] and Caucasians have higher incidence and mortality rates of NHL than patients in other ethnic groups. 1,2,5 During this period of time, treatment has improved, particularly with com-bination chemotherapy CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) [8][9][10][11][12][13][14][15][16] and later with the addition of rituximab to CHOP for Bcell NHL since 1998. [17][18][19][20] Although there were several studies that demonstrated ethnic disparities in receiving these treatments, [21][22][23] none of these studies has specifically addressed ethnic disparities in survival and whether these survival differences were due to disparities in treatment, diagnosis, or socioeconomic status (SES) or to other factors in patients with NHL.…”
mentioning
confidence: 99%
“…9 The median FFS ranged from 4.1 to 4.8 years, with a significant subset of patients (33%-44%) in remission at 15 years. 10 The nucleoside analog fludarabine used alone or in combination is highly active in FL. Based on encouraging results with fludarabine, mitoxantrone, and dexamethasone (FND) in relapsed FL, we conducted a randomized study to compare FND with ATT.…”
Section: A Short History Of Chemotherapy In Follicular Lymphomamentioning
confidence: 99%
“…Nearly every aforementioned regimen will result in a subset of patients who attain a molecular response and achieve durable remissions. 10 Long-term follow-up of several studies suggest that~30% to 40% of patients will not experience relapse despite decades of follow-up. 2,9,10 Furthermore, the rate of relapse appears to plateau between 8 and 10 years in most trials.…”
Section: A Short History Of Chemotherapy In Follicular Lymphomamentioning
confidence: 99%
See 1 more Smart Citation